Vascularized fibular epiphyseal transfer for proximal humeral reconstruction in children with a primary sarcoma of bone. (April 2018) - Stevenson, J. D.; Doxey, R.; Abudu, A.; Parry, M.; Evans, S.; Peart, F.; Jeys, L.
Abstract : Aims: Preserving growth following limb-salvage surgery of the upper limb in children remains a challenge. Vascularized autografts may provide rapid biological incorporation with the potential for growth and longevity. In this study, we aimed to describe the outcomes following proximal humeral reconstruction with a vascularized fibular epiphyseal transfer in children with a primary sarcoma of bone. We also aimed to quantify the hypertrophy of the graft and the annual growth, and to determine the functional outcomes of the neoglenofibular joint. Patients and Methods: We retrospectively analyzed 11 patients who underwent this procedure for a primary bone tumour of the proximal humerus between 2004 and 2015. Six had Ewing's sarcoma and five had osteosarcoma. Their mean age at the time of surgery was five years (two to eight). The mean follow-up was 5.2 years (1 to 12.2). Results: The overall survival at five and ten years was 91% (confidence interval (CI) 95% 75% to 100%). At the time of the final review, ten patients were alive. One with local recurrence and metastasis died one-year post-operatively. Complications included seven fractures, four transient nerve palsies, and two patients developed avascular necrosis of the graft. All the fractures presented within the first postoperative year and united with conservative management. One patient had two further operations for a slipped fibular epiphysis of the autograft, and a hemi-epiphysiodesis for lateral tibial physeal arrest. Hypertrophy and axial growth were evident in nine patients who did not have avascular necrosis of the graft. The mean hypertrophy index was 65% (55% to 82%), and the mean growth was 4.6 mm per annum (2.4 to 7.6) in these nine grafts. At final follow-up, the mean modified functional Musculoskeletal Tumour Society score was 77% (63% to 83%) and the mean Toronto Extremity Salvage Score (TESS) was 84% (65% to 94%). Conclusion: Vascularized fibular epiphyseal transfer preserves function and growth in young children following excision of the proximal humerus for a malignant bone tumour. Function compares favourably to other limb-salvage procedures in children. Longer term analysis is required to determine if this technique proves to be durable into adulthood. Cite this article: Bone Joint J 2018;100-B:535–41.